Strategy for the Development of the Sustainable Tourism Sector in the Coastal Area of Tomini Bay Based on Local Wisdom to Increase Regional Original Income In Bone Bolango Regency - Non Endey; I Kadek Satria Arsana; Lisda Van Gobel; Ansar Sahabi; Sabriana Oktaviana Gintulangi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The development of a sustainable tourism sector based on local wisdom will be a solution in formulating a strategy by looking at the tourism potential of the Tomini Bay coastal area which has an impact on increasing local revenue. This study aims to determine the strategy for developing the sustainable tourism sector in the coastal area of ​​​​Tomini Bay based on local wisdom to increase local revenue in Bone Bolango district. This research uses a qualitative descriptive research type. The focus of this research is strategies in the development of sustainable tourism in the form of attraction strategies, human resource strategies, service quality strategies, market strategies, and partnership strategies. Data were obtained from primary and secondary data through observation, interviews and documentation. Data analysis was carried out through the stages of data reduction, data presentation, drawing conclusions. As well as using a SWOT analysis that is used to develop a tourist attraction development strategy. The results showed that the management of the tourism sector in Bone Bolango district had not been well managed, this was caused by various problems, both internal and external. Meanwhile, regional original income through the tourism sector has not been fulfilled properly. Attractive strategy so far the existing tourist attraction objects are still natural. Judging from the human resource strategy in the form of a lack of human resources both in the tourism department and especially those in tourism objects. The strategy for the quality of coastal tourism services in the Tomini Bay district of Bone Bolango is still far from being satisfactory and does not yet have a good market strategy. The partnership strategy in tourism development has not been carried out by the regional government of Bone Bolango district because currently the focus of the local government, in this case the tourism sector, is more on improving documents.